THE DETERMINATIONS OF WILLINGNESS TO PAY TAXES - Eva Rianti Tenri Ajeng Tajuddin; Chermian Eforis (Ultimaccounting Jurnal Ilmu Akuntansi, 2023)
Abstract – This research aims to provide empirical evidence about the effect of knowledge of tax regulations, awareness of paying taxes, perception of tax system effectiveness, and quality of tax authorities' services toward a willingness to pay taxes. The object of this research is non-employee individual taxpayers registered at the tax service office in Jakarta and Banten. The sampling technique used is non-probability sampling with a convenience sampling method. This study uses primary data, personally administered questionnaires, and electronic and online questionnaires as data collection techniques. There are 138 questionnaires distributed, 131 returned questionnaires, and only 100 questionnaires that can be processed in this study using the multiple linear regression method. The result of this research is only knowledge of tax regulations has a significant positive effect on willingness to pay taxes. Awareness of paying taxes, perception of tax system effectiveness and quality of tax authorities services has no effect on willingness to pay taxes. Our findings indicate that the key point to increase willingness of taxpayer is with increase their knowledge of tax regulations without having to go to tax office or authority’s services. Keywords: Awareness; Knowledge; Perception; Services; Willingness.